Mewujudkan Kesejahteraan Sosial Bagi Pekerja Rumah Tangga Di Indonesia Ditinjau Dari Konsep Etika Persahabatan Aristoteles - Mauritius Damang; Pius Pandor (Journal Pendidikan Ilmu Pengetahuan Sosial, 2023)
The main focus of this writing is to analyze the concept of Aristotle's ethics of friendship in relation to efforts to achieve social well-being for domestic workers. Aristotle's concept of ethics of friendship is seen to have a contribution in upholding rights and realizing social well-being for domestic workers. The method used in this writing is literature study with a phenomenological approach, viewed from the perspective of Aristotle's ethics of friendship. The current phenomenon of life shows that domestic workers often do not receive legal protection and justice. The forms of injustice experienced by domestic workers include unjust wages, violence, and lack of social security. This happens because domestic workers are considered low-class workers who are exploited by employers for their own interests. This ultimately prevents domestic workers from experiencing well-being. The findings of this writing are that efforts to achieve social well-being for domestic workers can be realized if everyone realizes the presence of others as friends. Building friendship is very useful in maintaining harmony and creating well-being. This concept of friendship is ultimately crucial for domestic workers to ensure their rights and lead them to well-being. Friendship helps individuals to broaden their perspective that everyone has the same rights and dignity. This is capable of bringing human beings to well-being because its criterion lies in the well-being of each individual